Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

The question asks to find the derivative of the function $1-\cos(x)\sin(x)$, and I thought maybe using some derivative rules I could, but I don't know where to start.

share|cite|improve this question
Apply the rules: how to differentiate $f-g$, constant, then $f\cdot g$, finally you also need $\sin'=\cos$ and $\cos'=-\sin$. – Berci Oct 15 '12 at 0:56
up vote 4 down vote accepted

Are you familiar with the product rule? $$ f(x)=u(x)v(x)\\ f'(x)=u'(x)v(x) + u(x)v'(x) $$ In your case $u(x)=\cos(x), \ v(x)=\sin(x)$.

EDIT Sorry again for the typos, Here's what you should do. The derivative of constant is always 0, derivative of $-h(x)$ is $-h'(x)$, the derivative of a product of functions is above, the derivative of $\cos'(x)=- \sin(x), \ \sin'(x)=\cos(x)$

Can you handle it now?

EDIT 2: Sorry for doing it again, there is a different way of solving the problem if you notice that

$$ -\cos(x) \sin(x) = -\frac{2}{2}\cos(x) \sin(x)=-\frac{1}{2}\sin(2x) $$ and then use the chain rule: $\frac{du(v(x))}{dx} = u'(v(x))v'(x)$ and then use the derivative of the sin function

EDIT 3: OK here is the solution: $$ f'(x)=(-\cos(x)\sin(x))'_{x}=(-\frac{1}{2}\sin(2x))'_{x}=-\frac{1}{2}(2x)'_{x}\cos(2x)=-\cos(2x) $$

share|cite|improve this answer
you mean the product rule – Jean-Sébastien Oct 15 '12 at 0:53
@Alex : that is the product rule. We don't want to confuse the OP. Also, you can use "\sin" and "\cos". – Stefan Smith Oct 15 '12 at 0:54
Well, yes, you can rewrite it using $\sin(2x) = 2\sin(x)\cos(x)$ – Berci Oct 15 '12 at 0:57
Sorry for the typo, will update it now – Alex Oct 15 '12 at 0:58
I am not sure how you got the 2 in there? – Jillian Johnson Oct 15 '12 at 1:00

Using the well known trigonometric identity,


We can say that,


and the derivative would be:


share|cite|improve this answer
Upvoted for greatness. However, it won't help him in the long run because if he's asking this he clearly doesn't know about the product rule. – Damieh Oct 15 '12 at 15:10

$$(1 - \sin(x)\cos(x))' = \left(1 - \frac12 \sin(2x)\right)' = -\cos(2x).$$ Implicitly, I used the chain rule here, letting $f(x) = \sin(x)$ and $ g(x) = 2x$.

share|cite|improve this answer
Where did you get the -(1/2)sin(2x)?? – Jillian Johnson Oct 15 '12 at 1:13
Sorry, I dont know the chain rule. But thank you for helping. – Jillian Johnson Oct 15 '12 at 1:16
By using $\sin(2x) = 2\sin(x)\cos(x).$ – Ian Mateus Oct 15 '12 at 1:29
Got it, thanks! – Jillian Johnson Oct 15 '12 at 1:49

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.